Strategy for Competency Development of Civil State Apparatus in the New Normal Era in Wajo District - Rifdan Rifdan; Manan Sailan; Haerul Haerul (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
The purpose of this study is to analyze and discuss the implementation of Civil State Apparatus (CSA) CSA competency development in the Wajo Regency and formulate CSA Competency Development Strategies in the New Normal Era in Wajo Regency. The type of research used in this research is descriptive research using a qualitative approach. The research data sources are primary data sources and secondary data sources. The description of the focus of the research is the development of the competence of the CSA where there are 3 competencies (technical competence, managerial competence, and socio-cultural competence) which are carried out through education and training. The results showed that the development of CSA competence at the BKPSDM of Wajo Regency was seen from the Technical Competence, Managerial Competence, and Socio-cultural competence has not been optimal because competency development has not been implemented based on the results of the development needs analysis. So, the CSA competency development strategy must follow an integrated learning system (Corporate University).